O colecionador público documentalista: museu histórico e de ordem geral Plínio Travassos dos Santos de Ribeirão Preto - Espírito Santo, Silvia Maria do [UNESP] (2009)
The present thesis studies the contents of the development of the collections and the documentation on the museológica representation of the São Paulo West (São Paulo West, 1948-1958) in Brazil. The work also includes the analysis of the agent personality in the special example and the case on the creation process of the natural and official history museum and the coffee economy. Perhaps the economic and the material culture context, in this History Museum and general Order study, holds the aspects of the material body and the colecionismo processes, objects documentation and documents.